EDUKASI KONSERVASI MANGROVE BAGI KOMUNITAS TBM PALO PORONG DALAM MENCEGAH TERJADINYA ABRASI DI WILAYAH PESISIR PANTAI DI DESA KOLAKA, KABUPATEN FLORES TIMUR - Donata Peni (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Mangroves play a vital role in maintaining the balance of coastal ecosystems and provide ecological, economic, and social benefits to humans. However, some communities do not yet understand the importance of this ecosystem, resulting in various destructive practices, such as logging for firewood, land conversion to fishponds or salt fields, and dumping of garbage and waste into mangrove areas. If this situation continues, it will have serious impacts, one of which is coastal abrasion, which threatens the lives of coastal communities. To address this issue, this community service activity was conducted with the aim of educating and raising public awareness about the importance of mangrove conservation as an effort to prevent abrasion in coastal areas. The implementation method included interactive lectures, group discussions, and concrete actions such as planting mangroves in coastal areas. This activity involved the active participation of the local community, particularly children and adolescents from the Palo Porong Community Community Center (TBM Palo Porong), as agents of change in environmental conservation. The results of the activity showed an increase in public understanding and awareness of the function and benefits of the mangrove ecosystem. The community began to show behavioral changes that were more concerned with the environment, such as no longer cutting mangroves indiscriminately and participating in mangrove planting and maintenance activities. Furthermore, this activity fosters a spirit of mutual cooperation and social responsibility in preserving coastal natural resources. Therefore, it can be concluded that mangrove conservation education through a participatory approach can increase community ecological awareness and encourage sustainable, environmentally friendly behavior.